Wastewater treatment in vertical anaerobic filters for application in drip irrigation - Pitoro, Valdemiro Simão João [UNESP]; Lima, Tamires Da Silva [UNESP]; Román, Rodrigo Máximo Sánchez [UNESP]; Queluz, João Gabriel Thomaz [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2018)
Reusing wastewater (RA) in agriculture has been considered a common practice worldwide and an alternative to minimize the impacts of the current water scarcity scenario. However, the greatest limitation of the use of RA is its adequacy to the quality standards required by international guidelines. A water treatment system composed of six descending vertical flow anaerobic filters (AF), subdivided into two beds of equal number of filters with support material # 1 and # 4 has been studied under operational conditions with the objective of evaluating their performance in the treatment of RA for application in drip irrigation. The following parameters were analyzed: temperature, pH, electrical conductivity, turbidity, total solids, total suspended solids, dissolved total solids and biochemical oxygen demand. Results indicate that AF presented good performance, and the quality of the treated effluent (EFT) satisfies international and national guidelines for application in irrigation, except for BOD parameter. The risk of obstruction of drippers was classified as none by SST and SD parameters, and moderate for pH; turbidity and SST reduction above 97% were also observed. Although there were no significant differences in EFT quality among the support materials applied for most of t he analyzed parameters, the bed of filters with material support crushed # 1 presented better results, emphasizing the reduction of turbidity and SST.
Tratamento de água residuária em filtros anaeróbios verticais para aplicação na irrigação por gotejamento
Keywords: Obstruction of drippers; Reuse in agriculture; Treated sewage